The 12-item General Health Questionnaire (GHQ-12): translation and validation study of the Iranian version - Montazeri, Ali (BioMed Central, 2003)
BACKGROUND: The objective of this study was to translate and to test the reliability and validity of the 12-item General Health Questionnaire (GHQ-12) in Iran. METHODS: Using a standard 'forward-backward' translation procedure, the English language version of the questionnaire was translated into Persian (Iranian language). Then a sample of young people aged 18 to 25 years old completed the questionnaire. In addition, a short questionnaire containing demographic questions and a single measure of global quality of life was administered. To test reliability the internal consistency was assessed by Cronbach's alpha coefficient. Validity was performed using convergent validity. Finally, the factor structure of the questionnaire was extracted by performing principal component analysis using oblique factor solution. RESULTS: In all 748 young people entered into the study. The mean age of respondents was 21.1 (SD = 2.1) years. Employing the recommended method of scoring (ranging from 0 to 12), the mean GHQ score was 3.7 (SD = 3.5). Reliability analysis showed satisfactory result (Cronbach's alpha coefficient = 0.87). Convergent validity indicated a significant negative correlation between the GHQ-12 and global quality of life scores as expected (r = -0.56, P < 0.0001). The principal component analysis with oblique rotation solution showed that the GHQ-12 was a measure of psychological morbidity with two-factor structure that jointly accounted for 51% of the variance. CONCLUSION: The study findings showed that the Iranian version of the GHQ-12 has a good structural characteristic and is a reliable and valid instrument that can be used for measuring psychological well being in Iran.